The Role of Formyl Peptide Receptors for Immunomodulatory Activities of Antimicrobial Peptides and Peptidomimetics - Skovbakke, Sarah L.; Holdfeldt, Andre; Forsman, Huamei; Bylund, Johan; Franzyk, Henrik (Current Pharmaceutical Design, 2018)
In recent years, the therapeutic potential of antimicrobial peptides (AMPs) as immunomodulators has become generally accepted. Nevertheless, only very few AMP-based compounds have progressed into clinical trials. This paradox may be explained by the fact, that some of the intrinsic properties of natural peptides, such as proteolytic and oxidative instability, render them inconvenient as therapeutics. Therefore, substantial research efforts have been dedicated to mimic the physico-chemical properties as well as biological activities of AMPs by designing and identifying more stable peptidomimetics displaying analogous immunomodulatory activity profiles. Neutrophils play key roles in host defense as major effector cells in clearance of pathogens by phagocytosis and by regulating other processes of innate immunity as well as by promoting resolution of inflammation. Several aspects of these effects are correlated to their expression of formyl peptide receptors (FPRs) that have been shown to be targets of both natural and synthetic antimicrobial peptides. In the present review recent findings highlighting the role of FPRs in mediating immunomodulatory activities of natural and synthetic AMPs as well as of stabilized peptidomimetics are discussed, and prospects for future development of immunomodulatory therapeutics are presented.
Keywords: chemotaxis